2020
DOI: 10.1242/jeb.216770
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition and N2 solubility in triacylglycerol-rich adipose tissue: the likely importance of intact molecular structure

Abstract: Diving tetrapods (sea turtles, seabirds and marine mammals) are a biologically diverse group, yet all are under similar constraints: oxygen limitation and increased hydrostatic pressure at depth. Adipose tissue is important in the context of diving because nitrogen gas (N 2) is five times more soluble in fat than in blood, creating a potential N 2 sink in diving animals. Previous research demonstrates that unusual lipid composition [waxes and shortchained fatty acids (FA)] in adipose tissue of some whales lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 97 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…The key to function is likely the arrangement of the intact molecules relative to each other. Typically, intact TAG molecules are not sufficiently volatile for conventional GC analysis and their structures have therefore been described as the relative amounts of the constituent fatty acids (e.g., Gabler‐Smith et al, 2020; Straarup et al, 2006); these kinds of data do not inform the 3‐D or stereochemical structure of the TAG, which likely has more relevance for the functional aspects of the tissue in terms of acting as a structure to focus sound. It has been shown that the stereochemical structures of TAG molecules can alter physical properties (Karupaiah & Sundram, 2007) and that these do vary across lipids of different origins (Staarup et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key to function is likely the arrangement of the intact molecules relative to each other. Typically, intact TAG molecules are not sufficiently volatile for conventional GC analysis and their structures have therefore been described as the relative amounts of the constituent fatty acids (e.g., Gabler‐Smith et al, 2020; Straarup et al, 2006); these kinds of data do not inform the 3‐D or stereochemical structure of the TAG, which likely has more relevance for the functional aspects of the tissue in terms of acting as a structure to focus sound. It has been shown that the stereochemical structures of TAG molecules can alter physical properties (Karupaiah & Sundram, 2007) and that these do vary across lipids of different origins (Staarup et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, very little is known about intact TAG structure in marine lipids, and how variation in stereochemical structure might affect function in different animals. There is some evidence, for example, that intact TAG structure may be more important than FA composition in determining how nitrogen gas interacts with adipose tissue in diving tetrapods (Gabler‐Smith et al, 2020). Liquid chromatography coupled with mass spectrometry could be used in future studies to evaluate variation in both intact TAG and WE structures in the same topographical location.…”
Section: Discussionmentioning
confidence: 99%
“…The blood and tissue solubility of N 2 is very low, but similar in seals and humans (Kooyman, 1973). The N 2 solubility is approximately 5 times higher in lipids as compared to water and blood (Kooyman, 1973;Weathersby and Homer, 1980;Koopman and Westgate, 2012;Gabler-Smith et al, 2020), but the solubility differs considerably between lipid types where some deep diving species with a higher proportion of waxy esters have 73% higher N 2 solubility in blubber (Koopman and Westgate, 2012). In addition, not only does the τ tiss1/2 differ among tissues due to varying solubility and tissue volume, but it varies throughout the dive due to the changes in cardiac output, blood flow distribution, and the pulmonary shunt (Fahlman et al, 2006(Fahlman et al, , 2007(Fahlman et al, , 2019bZimmer and Tyack, 2007;Fitz-Clarke, 2009b).…”
Section: Ways To Manage Blood and Tissue Nmentioning
confidence: 99%
“…Given these observations, it is valuable to assess the potential risk of DCS within marine mammals. The work of McClelland et al (2012) , Gabler et al (2018) , and Gabler-Smith et al (2020) have demonstrated the potential for gas exchange and nitrogen embolism in some marine mammals in two tissues with high lipid content: blubber (the adipocyte-rich hypodermis covering the body) and acoustic fats (specifically, the fat bodies covering and surrounding the mandibles, associated with sound reception in echolocating odontocetes) ( Norris, 1968 ; Pond, 1998 ; Lonati et al, 2015 ). However, there is a lack of research dedicated to the spinal cord, the site of the more severe and potentially fatal Type II form of DCS.…”
Section: Introductionmentioning
confidence: 99%